Investigating intentionality of burning through macroscopic taphonomy in complex legacy funerary assemblages: Opportunities and challenges. (February 2022) - Evans, Miranda; Faulkner, Patrick; Asmussen, Brit
Highlights: Assessment of incidental and intentional burning of human bones in funerary context. Multi-method macroscopic, non-destructive taphonomic analysis of legacy assemblage. Analysis of potential cremations in Early Bronze Age Jericho Tomb A61. Results reveal complex processes of thermal modification, and funerary curation. Other Levant tombs bear similar evidence, suggesting regional similarities in practice. Abstract: Although there has been extensive experimental research on the thermal modification of bone, the results have rarely been applied to complex legacy funerary assemblages. The human skeletal remains from an Early Bronze Age IA tomb at Jericho were analysed to assess the utility of macroscopic taphonomic approaches both to interpreting intentionality in complex funerary practices involving the burning of human bones, and in understanding legacy assemblages that often lack the depth of contextual information available for their modern counterparts. These analyses generated valuable evidence for the interpretation of complex funerary practices in legacy assemblages, including the state of remains prior to burning, the approximate intensity of thermal modification and the deposition practice. This investigation highlights the value of non-destructive macroscopic taphonomic analysis as the foundation in the investigation of burning in complex legacy assemblages.